Being present: is it the most important communication skill? - Winarti, Oktifani; Mustikasari, Ratih Pandu; Nurhaqiqi, Hanna; Cretto-Bergerat, Valentin (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The COVID-19 pandemic has made people rely on the presence of the internet to run their business. Businesses, schools, retail, religious gatherings, and other components are all required to use an internet platform in some way. People can meet face-to-face and the feature of the contact is reinforced by both verbal and non-verbal communication prior to the viral eruption, making conversation much easier. The goal of this study is to emphasize the importance of being present during the COVID-19 Pandemic as well as the future projection of presence post-pandemic. Being present, as before the pandemic, comes effortlessly without conscious reflection because the interaction takes place offline without any restrictions. The result from this research that being present is the most crucial communication skill; it is the foundation of communication and can aid in more effective engagement on all levels (perception, comprehension, reasoning, memory, and production).